Energy Harvesting: Micropatterned P(VDF‐TrFE) Film‐Based Piezoelectric Nanogenerators for Highly Sensitive Self‐Powered Pressure Sensors (Adv. Funct. Mater. 21/2015). (June 2015) - Lee, Ju‐Hyuck; Yoon, Hong‐Joon; Kim, Tae Yun; Gupta, Manoj Kumar; Lee, Jeong Hwan; Seung, Wanchul; Ryu, Hanjun; Kim, Sang‐Woo
Abstract : S.‐W. Kim and co‐workers report a novel highly sensitive piezoelectric nanogenerator (PNG) for self‐powered pressure sensors based on a micro‐patterned piezoelectric polymer P(VDF‐TrFE) thin film. The micro‐structured PNGs presented on page 3203 has five times larger output power compared to the flat film‐based PNG. The micro‐structured PNG shows high sensitivity and mechanical durability under various circumstances such as rain drop and wind blow.